Determinants of Adherence to Taking Antihypertensive Drugs Based on the Health Promotiom Model (HPM); A Systematic Scoping Review - Juanda Sitepu; Cau Kim Jiu; Lidia Hastuti; Suriadi Jais; Hariyanto Hariyanto (Jurnal Keperawatan Profesional, 2026)
Adherence to antihypertensive medication is a key determinant of successful blood pressure control and the prevention of cardiovascular complications. However, empirical evidence indicates that medication adherence among patients with hypertension remains suboptimal. Therefore, a comprehensive and theory-based approach is required to better understand the factors influencing adherence behavior. This study aimed to map and synthesize scientific evidence on factors influencing adherence to antihypertensive medication based on the Health Promotion Model (HPM). This study employed a systematic scoping review design following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Scoping Reviews (PRISMA-ScR) guidelines. Relevant articles published between 2020 and 2025 were systematically selected according to predefined inclusion and exclusion criteria. The findings revealed that key HPM constructs significantly associated with adherence to antihypertensive medication included perceived benefits, self-efficacy, perceived barriers, and interpersonal influences. Among these constructs, perceived benefits and self-efficacy were the most consistently and strongly reported determinants across the reviewed studies. The Health Promotion Model is a relevant and applicable theoretical framework for understanding and improving adherence to antihypertensive medication through promotive and preventive nursing interventions.